2022
DOI: 10.1007/s13555-022-00833-8
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Dermatology: Challenges and Perspectives

Abstract: Artificial intelligence (AI) based on machine learning and convolutional neuron networks (CNN) is rapidly becoming a realistic prospect in dermatology. Non-melanoma skin cancer is the most common cancer worldwide and melanoma is one of the deadliest forms of cancer. Dermoscopy has improved physicians’ diagnostic accuracy for skin cancer recognition but unfortunately it remains comparatively low. AI could provide invaluable aid in the early evaluation and diagnosis of skin cancer. In the last decade, there has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 85 publications
0
27
0
Order By: Relevance
“…Dermatologists can also apply this method for disease diagnosis. For example, an image is annotated according to the corresponding medical records and pathological results and, after generating standardized data, these data can then be analyzed using CNN to distinguish and thus diagnose skin lesion images from that of normal skin images ( Haenssle et al, 2018 ; Liopyris et al, 2022 ). This method is often used in the diagnosis of fungal infections, such as onychomycosis, as this condition represents the most common nail disease infected with fungi.…”
Section: Recognition Of Fungi With Convolutional Neural Networkmentioning
confidence: 99%
“…Dermatologists can also apply this method for disease diagnosis. For example, an image is annotated according to the corresponding medical records and pathological results and, after generating standardized data, these data can then be analyzed using CNN to distinguish and thus diagnose skin lesion images from that of normal skin images ( Haenssle et al, 2018 ; Liopyris et al, 2022 ). This method is often used in the diagnosis of fungal infections, such as onychomycosis, as this condition represents the most common nail disease infected with fungi.…”
Section: Recognition Of Fungi With Convolutional Neural Networkmentioning
confidence: 99%
“…Dear Editor, Artificial intelligence (AI) based on machine learning and convolutional neuron networks is rapidly becoming a realistic prospect in Dermatology. 1,2 Due to the unique nature of Dermatology, AI-aided dermatological diagnosis based on image recognition has become a current focus and future trend. 3 In recent studies, AI algorithms have shown promising results for diagnosing non-melanoma skin cancer and melanoma, with a diagnostic accuracy comparable with that of skin experts.…”
Section: Phototherapy In the Artificial Intelligence Eramentioning
confidence: 99%
“…3 In recent studies, AI algorithms have shown promising results for diagnosing non-melanoma skin cancer and melanoma, with a diagnostic accuracy comparable with that of skin experts. [1][2][3] The use of 3D imaging systems allows clinicians to screen and label skin-pigmented lesions and distributed disorders, which can provide an objective assessment and image documentation of lesion sites. 3 Dermatoscopes combined with intelligent software help the dermatologist to easily correlate each close-up image with the corresponding marked lesions in the 3D body map.…”
Section: Phototherapy In the Artificial Intelligence Eramentioning
confidence: 99%
See 2 more Smart Citations